Central bank regulation, religious governance and standardisation: evidence from Malaysian Islamic banks - Sheikh Hassan, Ahmad Fahmi; Karbhari, Yusuf; Ahmed, Habib (Inderscience Publishers, 2021)
This study explores the modus operandi and regulatory influence of the pioneering Malaysian dual-layer governance system where, besides an Islamic bank's in-house religious board, supervision is undertaken by the country's central bank via its own Shariah Advisory Council (SAC). Data was collected by means of in-depth interviews with SAC members, central bank compliance officers, bank chairmen and members of Shariah boards, CEO's and other senior executives. We find that the procedures asserted by this over-arching governance structure contributes to standardising practice without hampering creativity when innovating new Shariah compliant financial products. Considerable bureaucracy is reported to exist due to the current approval process impeding efficient decision-making. In particular, the SAC is found to be decisive in resolving disputes from the widespread use of the 'legal reasoning' (or ijtihad) principle exercised by boards providing the much needed confidence and market discipline required by stakeholders. Finally, we highlight how this form of banking operates best when left to a country's own governance framework rather than imposing international regulation for this nascent industry.